Capitalism without Democracy : The Private Sector in Contemporary China - Tsai, Kellee S. (Book collections on Project MUSE., 2007)
Based on years of research, hundreds of field interviews, and a sweeping nationwide survey of private entrepreneurs, this text explodes the conventional wisdom about the relationship between economic liberalism and political freedom.